Certification, good agricultural practice and smallholder heterogeneity: Differentiated pathways for resolving compliance gaps in the Indonesian oil palm sector - Schoneveld, George C.; Haar, S. van der; Ekowati, D.; Andrianto, A.; Komarudin, Heru; Okarda, B.; Jelsma, I.; Pacheco, P. (Elsevier, 2019)
Enhancing smallholder compliance with sustainability standards and good agricultural practices features prominently on the global sustainability agenda. Operating in a sector that bears intense public scrutiny, Indonesia’s oil palm smallholders are especially confronted by pressures to enhance their environmental performance. Because smallholders experience differentiated compliance barriers however, it is widely recognized that for the purpose of more effectively prioritizing and targeting the necessary intervention support, smallholder heterogeneity needs to be better understood. This is especially the case for independent – in contrast to ‘plasma’ - oil palm smallholders, for whom corporate technical, input and financial support is comparatively inaccessible. Through multivariate analysis, this article contributes to these needs by developing a typology of independent oil palm smallholders in Indonesian Borneo. We subsequently model the predicted probabilities of different types of smallholders complying with Indonesia’s major national sustainability standard and select indicators of good agricultural practice. This analysis reveals structural compliance gaps, which threatens to restrict smallholder access to formal markets in future. In showing that intervention strategies to resolve these compliance gaps can be more impactful when these are adapted to smallholder livelihood assets, portfolios and strategies, this article points to the importance of more explicitly accounting for socio-economic differentiation when addressing contemporary smallholder upgrading challenges. With results however revealing how local entrepreneurs and elites complicit in regulatory evasion and illegal land encroachments play a significant role in the sub-sector, local political resistance to initiatives that aim to bring the sub-sector above board can be anticipated. This highlights how institutional building needs to be more explicitly incorporated into the design of smallholder-centric intervention strategies; through, for example, the adoption of more integrative landscape-level planning approaches.